HIV sexual transmission risks in the context of clinical care: a prospective study of behavioural correlates of HIV suppression in a community sample, Atlanta, GA, USA. Issue 1 (5th August 2015) - Kalichman, Seth C; Cherry, Chauncey; Kalichman, Moira O; Washington, Christopher; Grebler, Tamar; Merely, Cindy; Welles, Brandi; Pellowski, Jennifer; Kegler, Christopher
Abstract : Introduction: Antiretroviral therapy (ART) improves the health of people living with HIV and has the potential to reduce HIV infectiousness, thereby preventing HIV transmission. However, the success of ART for HIV prevention hinges on sustained ART adherence and avoiding sexually transmitted infections (STI). Objectives: To determine the sexual behaviours and HIV transmission risks of individuals with suppressed and unsuppressed HIV replication (i.e., viral load). Methods: Assessed HIV sexual transmission risks among individuals with clinically determined suppressed and unsuppressed HIV. Participants were 760 men and 280 women living with HIV in Atlanta, GA, USA, who completed behavioural assessments, 28‐daily prospective sexual behaviour diaries, one‐month prospective unannounced pill counts for ART adherence, urine screening for illicit drug use and medical record chart abstraction for HIV viral load. Results: Individuals with unsuppressed HIV demonstrated a constellation of behavioural risks for transmitting HIV to uninfected sex partners that included symptoms of STI and substance use. In addition, 15% of participants with suppressed HIV had recent STI symptoms/diagnoses, indicating significant risks for sexual infectiousness despite their HIV suppression in blood plasma. Overall, 38% of participants were at risk for elevated sexual infectiousness and just as many engaged in unprotected sexual intercourse with non‐HIV‐infected partners. Conclusions: Implementation strategies for using HIV treatments as HIV prevention requires enhanced behavioural interventions that extend beyond ART to address substance use and sexual health that will otherwise undermine the potential preventive impact of early ART.